Differentiation between Shallow and Deep Charge Trap States on Single Poly(3‐hexylthiophene) Chains through Fluorescence Photon Statistics. Issue 17 (22nd October 2015) - Grußmayer, Kristin S.; Steiner, Florian; Lupton, John M.; Herten, Dirk‐Peter; Vogelsang, Jan
Abstract: Blinking of the photoluminescence (PL) emitted from individual conjugated polymer chains is one of the central observations made by single‐molecule spectroscopy (SMS). Important information, for example regarding excitation energy transfer, can be extracted by evaluating dynamic quenching. However, the nature of trap states, which are responsible for PL quenching, often remains obscured. We present a detailed investigation of the photon statistics of single poly(3‐hexylthiophene) (P3HT) chains obtained by SMS. The photon statistics provide a measure of the number and brightness of independently emitting areas on a single chain. These observables can be followed during blinking. A decrease in PL intensity is shown to be correlated with either 1) a decrease in the average brightness of the emitting sites; or 2) a decrease in the number of emitting regions. We attribute these phenomena to the formation of 1) shallow charge traps, which can weakly affect all emitting areas of a single chain at once; and 2) deep traps, which have a strong effect on small regions within the single chains. Abstract : Shallow or deep? Photoluminescence (PL) blinking of single conjugated polymer chains, due to interaction of the exciton with a trapped charge, is a central observation made by single‐molecule spectroscopy. Close inspection of the photon statistics during PL quenching allows differentiation between shallow and deep trap states. Charges trapped in shallow states interact with the entire chain and do not affect the number of emitters on the chain.